Comparative Effectiveness of After-School Programs to Increase Physical Activity - Sabina B. Gesell; Evan C. Sommer; E. Warren Lambert; Ana Regina Vides de Andrade; Lauren Whitaker; Lauren Davis; Bettina M. Beech; Stephanie J. Mitchell; Nkiruka Arinze; Stevon Neloms; Colleen K. Ryan; Shari L. Barkin (Journal of Obesity)
Background. We conducted a comparative effectiveness analysis to evaluate the difference in the amount of physical activity children engaged in when enrolled in a physical activity-enhanced after-school program based in a community recreation center versus a standard school-based after-school program. Methods. The study was a natural experiment with 54 elementary school children attending the community ASP and 37 attending the school-based ASP. Accelerometry was used to measure physical activity. Data were collected at baseline, 6 weeks, and 12 weeks, with 91% retention. Results. At baseline, 43% of the multiethnic sample was overweight/obese, and the mean age was 7.9 years (SD = 1.7). Linear latent growth models suggested that the average difference between the two groups of children at Week 12 was 14.7 percentage points in moderate-vigorous physical activity (P<.001). Cost analysis suggested that children attending traditional school-based ASPs—at an average cost of $17.67 per day—would need an additional daily investment of $1.59 per child for 12 weeks to increase their moderate-vigorous physical activity by a model-implied 14.7 percentage points. Conclusions. A low-cost, alternative after-school program featuring adult-led physical activities in a community recreation center was associated with increased physical activity compared to standard-of-care school-based after-school program.